Experimental estimation of the performance of the homemade single slop Solar distilled - Yaseen H. Mahmood; Abeer Ibrahim. Ashawi (Tikrit Journal of Pure Science, 2022)
Water pollution and scarcity have created problems in all aspects of life, especially in poor countries. In This work the fabricated of a single slop distilled from cheap materials, with a glass lid for use for desalination. The study noted that solar radiation is of good magnitude in the study area for the implementation of solar energy projects. The solar-drip production increases with increased solar radiation, which increases the efficiency of the distilled, and the reduction of the water level in the basin decreases the speed of productivity and increases it, where efficiency was 40%, at the highest in the experiments 1.5 mm then rose to 50% at 1mm and increased to more than 65% at 0.5 mm.